Incorporating Business English in the EFL Curriculum - Naumoska Sarakinska, Biljana (South East European University, Tetovo, 2020)
ESP, that is, English for Specific Purposes, is an important subbranch of English-learning, especially in today’s fast-paced and everchanging world, where progress is key, and advances are rapid in all spheres. The term itself refers, in fact, to the study of English as an EFL or ESL, at a university level, or by already-employed people, dealing with the specific vocabulary and skills of a given field. As opposed to General English, or EGP (English for General Purposes), ESP tends to be aimed for and designed more toward adult learners, as well as to learners that have attained at least an intermediate level of proficiency. However, besides the numerous advantages that ESP offers, both teaching- and learning-wise, there are also some issues that may arise, and that might be worth looking into in more detail, in order to maximize the teaching and learning experience. For example, learners that have been grouped together but differ in terms of their level of EFL proficiency, establishing the focus of the classes, such as whether it is going to be more grammar-oriented or more skills-focused, then, assessment issues, choosing the most appropriate classroom materials, large-sized groups, among others, are all challenges that are likely to occur, and are bound to need to be addressed and dealt with. This paper focuses on taking a closer look at various aspects of ESP, specifically Business English, in terms of incorporating it in the EFL curriculum, the above-mentioned challenges that might be encountered, and the reasons for them, as well as the ways with which they can be alleviated, and resolved.
Keywords: ESP, EFL, ESL, EGP, Business English